Identification of two novel and one rare mutation in DYRK1A and prenatal diagnoses in three Chinese families with intellectual Disability-7 - Huang, Cheng; Luo, Haiyan; Zeng, Baitao; Feng, Chuanxin; Chen, Jia; Yuan, Huizhen; Huang, Shuhui; Yang, Bicheng; Zou, Yongyi; Liu, Yanqiu (Frontiers in Genetics, 2023)
Background and purpose: Intellectual disability-7 (MRD7) is a subtype disorder of intellectual disability (MRD) involving feeding difficulties, hypoactivity, and febrile seizures at an age of early onset, then progressive intellectual and physical development deterioration. We purposed to identify the underlying causative genetic factors of three individuals in each Chinese family who presented with symptoms of intellectual disability and facial dysmorphic features. We provided prenatal diagnosis for the three families and genetic counseling for the prevention of this disease. Methods: We collected retrospective clinical diagnostic evidence for the three probands in our study, which included magnetic resonance imaging (MRI), computerized tomography (CT), electroencephalogram (EEG), and intelligence tests for the three probands in our study. Genetic investigation of the probands and their next of kin was performed by Trio-whole exome sequencing (WES). Sanger sequencing or quantitative PCR technologies were then used as the next step to verify the variants confirmed with Trio-WES for the three families. Moreover, we performed amniocentesis to explore the state of the three pathogenic variants in the fetuses by prenatal molecular genetic diagnosis at an appropriate gestational period for the three families. Results: The three probands and one fetus were clinically diagnosed with microcephaly and exhibited intellectual developmental disability, postnatal feeding difficulties, and facial dysmorphic features. Combining probands’ clinical manifestations, Trio-WES uncovered the three heterozygous variants in DYRK1A: a novel variant exon3_exon4del p.(Gly4_Asn109del), a novel variant c.1159C>T p.(Gln387*), and a previously presented but rare pathogenic variant c.1309C>T p.(Arg437*) (NM_001396.5) in three families, respectively. In light of the updated American College of Medical Genetic and Genomics (ACMG) criterion, the variant of exon3_exon4del and c.1159C>T were both classified as likely pathogenic (PSV1+PM6), while c1309C>T was identified as pathogenic (PVS1+PS2_Moderate+PM2). Considering clinical features and molecular testimony, the three probands were confirmed diagnosed with MRD7. These three discovered variants were considered as the three causal mutations for MRD7. Prenatal diagnosis detected the heterozygous dominant variant of c.1159C>T p.(Gln387*) in one of the fetuses, indicating a significant probability of MRD7, subsequently the gestation was intervened by the parents’ determination and professional obstetrical operation. On the other side, prenatal molecular genetic testing revealed wild-type alleles in the other two fetuses, and their parents both decided to sustain the gestation. Conclusion: We identified two novel and one rare mutation in DYRK1A which has broadened the spectrum of DYRK1A and provided evidence for the diagnosis of MRD7 at the molecular level. Besides, this study has supported the three families with MRD7 to determine the causative genetic factors efficiently and provide concise genetic counseling for the three families by using Trio-WES technology.